1985
DOI: 10.1002/pssb.2221290124
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Decay from Free and Bound Excitons in GaSe

Abstract: Spontaneous excitonic luminescence in GaSe is investigated from 80 to 300 K and a t weak laser excitation intensity. Radiative recombinations of direct and indirect free excitons are clearly observed. The analysis of the emission lines as a function of the temperature, of the excitation intensity, and of laser energy permits to attribute two lines of the intrinsic luminecsence to the recombination of direct and indirect excitons bound to defect centres localized in the energy gap. On the basis of recent theori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…When the temperature is high enough for the electrons in ICB to acquire the energy E , =: E,, -EICB, then the scattering couples the states k = ki and k = 0 and electrons from IC'B populate the FE state. Recent studies of photoluminescence spectra of GaSe crystals [24] confirm the model [23] and it was shown that energy redistribution between emission from direct and indirect bands with increasing temperature 2 80 K was observed.…”
Section: Discussionmentioning
confidence: 64%
“…When the temperature is high enough for the electrons in ICB to acquire the energy E , =: E,, -EICB, then the scattering couples the states k = ki and k = 0 and electrons from IC'B populate the FE state. Recent studies of photoluminescence spectra of GaSe crystals [24] confirm the model [23] and it was shown that energy redistribution between emission from direct and indirect bands with increasing temperature 2 80 K was observed.…”
Section: Discussionmentioning
confidence: 64%
“…From eqs (15). and(16) it is seen that inequality (14) contains the half-width G,4bam HH2 $ f exc aG 2 X 17…”
mentioning
confidence: 99%
“…The ratio of the strain localized GaSe PL to the band edge emission X E g is significantly enhanced by two orders of magnitude on the pillars. At a much lower laser power density of 44 nW/μm 2 , PL spectra measured at T = 3.5 K on the pillars exhibited a few strong and well-separated features without the broad background or additional defect-related bands that are often observed in WSe 2 and hBN. , For example, in Figure c, the PL spectrum collected from GaSe on a pillar shows a single peak X S at ∼1.90 eV (∼652 nm), about ∼0.15 eV below the well-studied GaSe band edge emission X E g at 2.05 eV. Note that the emission energies of GaSe SPEs measured here are consistent with previous study on GaSe SPEs associated with strain developed on GaSe film on randomly distributed selenium clusters …”
Section: Resultsmentioning
confidence: 92%